Thomas Kuhn's 'Linguistic Turn' and the Legacy of Logical Empiricism : Incommensurability, Rationality and the Search for Truth - Gattei, Stefano (Ashgate New Critical Thinking in Philosophy, 2016)
Presenting a critical history of the philosophy of science in the twentieth century, focusing on the transition from logical positivism in its first half to the ""new philosophy of science"" in its second, Stefano Gattei examines the influence of several key figures, but the main focus of the book are Thomas Kuhn and Karl Popper. Gattei makes two important claims about the development of the philosophy of science in the twentieth century; that Kuhn is much closer to positivism than many have supposed, failing to solve the crisis of neopostivism, and that Popper, in responding to the deeper cri.